Efektivitas Penanganan Barang Bawaan Tamu Tiba Pada Saat Peak Hours di Hotel Prama Sanur Beach Bali - Andika, Kadek Dwi Weda Andika; Wulan, Anak Agung Istri Ratna Sari; Sunarsa, I Wayan (Program Studi Manajemen Divisi Kamar, 2024)
This study aims to determine the effectiveness of handling guests' luggage arriving during peak hours at the Prama Sanur Beach Hotel Bali. Data were obtained by interview, documentation and observation checklist techniques. The data that has been collected and then analyzed using qualitative descriptive analysis techniques, namely by describing the facts in the field in the form of the results of the implementation of standard operating procedures (SOP) for handling luggage for arriving guests carried out by bellboy officers at the Prama Sanur Beach Hotel Bali.The results of the analysis show that as many as seven steps of procedures for handling luggage for arriving guests have been implemented in accordance with the applicable standard operating procedures. Meanwhile, as many as four steps of the procedure for handling luggage for arriving guests have not been implemented in accordance with standard operating procedures. Procedures for handling luggage for arriving guests that have not been implemented include: not preparing a trolley and checking the condition of the trolley, not checking and counting the luggage of arriving guests, not explaining the facilities in the room and not offering assistance to guests before leaving the room. Therefore, the bell captain is expected to increase supervision of bellboy officers to be more obedient in carrying out their work because the guest experience is a thing that must be considered to maintain brand awareness of an accommodation.